Evaluation of clinical parameters for detection of early endpoint criteria in guinea pigs experimentally infected with Mycobacterium tuberculosis - Williams, Wendy R., author; Izzo, Angelo, advisor; Kendall, Lon, committee member; Johnston, Matt, committee member (Colorado State University. Libraries, 2015)
Tuberculosis (TB) is a global epidemic caused by the bacteria Mycobacterium tuberculosis. Despite extensive research and funding to improve diagnostic and treatment strategies, the emergence of multi drug resistant and extensively drug resistant strains of M. tuberculosis are on the rise. Vaccines present a solution to the failing diagnostic and treatment strategies by preventing incidence of disease. Guinea pigs are a common animal model to test TB vaccine candidates, but are difficult to evaluate in terms of overall health status. We hypothesized that using parameters within the complete blood count, serum biochemistry, and urinalysis assays we would identify biomarkers that could be used as early endpoint criteria for guinea pigs experimentally infected with M. tuberculosis. Using groups of BCG-vaccinated or saline-treated guinea pigs we measured biomarkers over the life of guinea pigs both pre-challenge and after challenge with laboratory strain M. tuberculosis H37Rv. Our study showed significant differences between groups of guinea pigs, as well as compared to pre-challenge values. Specifically, blood urea nitrogen, urine specific gravity, serum proteins, alanine transferase, hematocrit, leukocytes, and body weight should be monitored when establishing early endpoint criteria in guinea pigs experimentally infected with M. tuberculosis.